Answer:
y = (x-3)^2 - 17
Step-by-step explanation:
To complete the square, take the middle term bx and divide it in two. Then take the square.
x^2 - 6x - 8 has bx = -6x. Take -6/2 = -3. Square -3^2 = 9.
Now to finish completing the square add 9 and subtract 9 from one side.
y = x^2 - 6x - 8
y = (x^2 - 6x +9) -9 - 8
y = (x-3)^2 - 17
Answer:
Step-by-step explanation:
m∠2 = 52° [Alternate interior angles]
m∠1 + m∠2 = 180° [Linear pair of angles are supplementary]
m∠1 = 180° - 52°
m∠1 = 128°
m∠3 = 47° [Alternate interior angles]
m∠5 + 52° + 47° = 180° [Sum of linear angles is 180°]
m∠5 = 180° - 99°
= 81°
m∠4 + 47° = 180° [Sum of consecutive interior angles is 180°]
m∠4 = 180° - 47°
m∠4 = 137°
$13.53 is the answer to you problem